2020
DOI: 10.4285/kjt.2020.34.2.71
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation in Asia during the coronavirus disease-19 (COVID-19) pandemic: briefs from member countries of the Asian Society of Transplantation

Abstract: The coronavirus disease-19 (COVID-19) pandemic has affected 1,029,968 people in Asia as of May 16, 2020. Although Asia was the first continent to be affected, many countries in the region continue to battle COVID-19, which challenges the way transplant programs provide their services. Given the diversity of healthcare systems in Asia, the countermeasures in response to COVID-19 are as potentially diverse. This review reports the experiences of transplant services in member countries of the Asian Society of Tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…As it underwent lockdown on March 2020, all transplant centers ceased performing procedures to minimize the exposure of transplant patients to COVID-19. Deceased donor procurement activities were also suspended 9 . While some of the institutions have resumed performing a limited number of procedures this year, kidney transplantation in the country is effectively stifled for the foreseeable future.…”
Section: Kidney Transplantation Comes To a Standstillmentioning
confidence: 99%
“…As it underwent lockdown on March 2020, all transplant centers ceased performing procedures to minimize the exposure of transplant patients to COVID-19. Deceased donor procurement activities were also suspended 9 . While some of the institutions have resumed performing a limited number of procedures this year, kidney transplantation in the country is effectively stifled for the foreseeable future.…”
Section: Kidney Transplantation Comes To a Standstillmentioning
confidence: 99%
“…Organ donation and transplantation in Asia have been adversely affected by the COVID-19 pandemic but to varying degrees. Most countries had elected to shut down transplant services, but some countries permitted deceased donors and urgent transplantation to continue, such as Hong Kong, Malaysia, and Singapore [ 17 ]. Noticeably, South Korea had most transplant programs remaining active during this time, which may account for the high rate of transplants being performed during the first 3 months of 2020 [ 18 ].…”
Section: Adapting To Covid-19 In Transplant Healthcare Systems In Asiamentioning
confidence: 99%
“…Despite the increased risks, most patients reported that they would choose immediate transplantation if there was no foreseeable end to the pandemic, especially if the medical urgency did not permit further delays. Finally, there is reassurance that the rate and mortality of COVID-19 infections in transplant recipients in Asia appear to be low [ 8 , 17 ]. This could be related to the pre-emptive defensive measures adopted by Asian transplant programs for their patients during this period, which was consistent across different Asian countries ( Table 1 ) [ 17 ].…”
Section: Adapting To Covid-19 In Transplant Healthcare Systems In Asiamentioning
confidence: 99%
“…As of December 1, 2021, there are 82,141,978 cases of COVID-19 in Asia. This represents the highest case load among all continents, thus making Asia the new global epicenter of COVID- 19. Many transplant programs in Asia were either shut down or overwhelmed by the increasing incidence of COVID-19 cases; therefore, transplantation in Asia, which is a region with already low transplantation rates, was dealt another huge blow by the COVID-19 pandemic [1]. However, there is paucity of data on morbidity and mortality from COVID-19 involving transplant recipients in Asia.…”
Section: Introductionmentioning
confidence: 99%